SATISFACTION OF IBNU SINA UNIVERSITY’S STUDENTS BASED ON ANALYSIS OF ACADEMIC SERVICE QUALITY - Mulyadi; Fadlilah, Andi Hidayatul; Mustaqim, Haji; Sabri; Sumardin; Sudianto (International Journal of Psychosocial Rehabilitation, 2020)
Universities should provide maximum services and match the wishes of students. One sign of the good university can be seen from the Lecturers and service staff in Education. The existence of good quality in Education and Education services provide maximum results so that students feel satisfied with the service. In fact, the University still has many obstacles that result in dissatisfaction of students. The problem is focused on an academic preparedness service and infrastructure whose evaluation is still lacking. Academic handling problems that become obstacles for students such as lecture schedules, lecture schedules are less consistent, Lecturers are too busy, the slow announcement of Grades on Exams, lack of transparency in grades, and difficult to relate to certain Lecturers in guiding the preparation of the final project. Based on these problems, research is needed in the field of quality of education services and seeks to improve service satisfaction for students at the university. The type of this research is descriptive quantitative approach and research focus of Management study program, Ibnu Sina University. The observations carried out as a survey method with a population of respondents were 36 students. The technique used includes a sample of nonprobability sampling technique by purposive sampling. Data collection techniques used was questionnaires and documentation. The results showed that the dimensions of Reliability and Responsiveness obtained the lowest percentage value (71.35%), followed by the Assurance dimension of 73.13%, and Empathy of 73.74%, while the highest score obtained by the Tangible dimension of 81.25%.